Exploring the Dynamics and Potential Outcomes of an Integrated Land Information System for Land Development - A Case Study of Johannesburg's Land Information System - Momberg, Mark (My University, 2014)
As we delve deeper into the 21st century, the progressive diffusion of technology in our daily lives is becoming more apparent. The world is fundamentally changed due to the relentless pace and nature of technological advancements. Governments across the globe have recognised the importance of information technology in information management and public sector reform. Information technologies allow government to capture, store and maintain large volumes of information. This shift towards an electronically driven government has facilitated the implementation of information systems. With society becoming increasingly connected and spatially enabled, the expectation of government to perform has increased significantly. Access to reliable and efficient information is the cornerstone of the planning profession. The sharing of information electronically has an enormous potential for integration and coordination in planning within government. This report seeks to accentuate the immense potential of a Land Information System. These systems hold much potential for the contemporary planner. The research identified the importance of information in the realm of planning, as the basic resource in any decision making process. It is argued that the majority of local government functions are dependent on the same property data and that an integrated information system can enhance the effectiveness and efficiency of the decision making process in land development. The City of Johannesburg was the first metropolitan municipality in South Africa to undertake such an initiative. Through information integration, it was possible to implement a revolutionary database as a single source of property information. This research seeks to uncover the dynamics and potential outcomes of such a system. It uncovered how an integrated information system can be utilised to mechanise, optimise and revolutionise information usage. Land development could be enhanced through the implementation of a Land Information System, which involves process of property data collection.
Planning Honours Research Report 2014, Wits University
Keywords: land information, land development, government